A bibliometric review of online impulse buying behaviour. (8th February 2022) - Bashar, Abu; Singh, Shalini; Pathak, Vivek Kumar
Online impulse buying behaviour is one of the most rapidly growing areas of research in online consumer behaviour study. Since the last two decades, it has achieved significant academic attention and developed publication opportunities. This paper presents bibliometric review of scientific literature in the field of online impulse buying behaviour. For this, 482 articles from Scopus database during 2000-2020 are considered. Three major research streams found and reviewed i.e.: a) online store characteristics; b) modelling of online impulse buying behaviour; c) factors influencing impulsive buying in online setup. Most relevant and influential authors, countries, affiliations, most cited documents, and most used keywords are identified. The paper suggests certain future research agenda in online impulse buying behaviour that have been determined from bibliometric analysis. This study offers practical implications for both academicians and practitioners.